2021
DOI: 10.1177/2325967120973284
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Platelet-Rich Plasma in the Treatment of Knee Osteoarthritis: A Meta-analysis of Randomized Controlled Clinical Trials

Abstract: Background: The effectiveness of platelet-rich plasma (PRP) injections for knee osteoarthritis and the effects of leukocyte-poor PRP (LP-PRP) versus leukocyte-rich PRP (LR-PRP) are still controversial. Purpose: To assess the effectiveness of different PRP injections through a direct and indirect meta-analysis of randomized controlled trials. Study Design: Systematic review; Level of evidence, 1. Methods: A systematic literature search of electronic databases (PubMed, Cochrane Library, and EMBASE) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
(58 reference statements)
1
30
1
2
Order By: Relevance
“…This seems natural because if the KOA worsens, the efficacy of PRP therapy may decrease. Interestingly, most previous studies concluded that the severity of KOA was not associated with the efficacy of PRP therapy [ 4 , 5 , 13 ]. This could be attributed to the fact that most previous prospective studies excluded patients with severe KOA (KL grade 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This seems natural because if the KOA worsens, the efficacy of PRP therapy may decrease. Interestingly, most previous studies concluded that the severity of KOA was not associated with the efficacy of PRP therapy [ 4 , 5 , 13 ]. This could be attributed to the fact that most previous prospective studies excluded patients with severe KOA (KL grade 4).…”
Section: Discussionmentioning
confidence: 99%
“…PRP therapy is the most frequently used cell-based therapy for KOA because it is simple, minimally invasive, inexpensive, and has fewer complications than arthroplasty [ 3 ]. A meta-analysis of clinical trials involving intra-articular (IA) PRP injection in patients with KOA demonstrated that PRP has favorable effects on improving pain and functional scores compared with HA, steroid, and saline injections [ 4 , 5 ]. A meta-analysis of 21 randomized controlled clinical trials (RCTs) demonstrated that a clinically important benefit for pain relief was seen for intra-articular PRP compared with intra-articular saline (standardized mean difference (SMD) = −1.38 (95% CI, −2.07 to −0.70); p < 0.0001; I 2 = 37%) and corticosteroid solution injections (SMD = −2.47 (95% CI, −3.34 to −1.61); p < 0.00001; I 2 = 47%) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Injections of blood-derived products are a widely diffused treatment for KOA, and increasing evidence shows their safety and efficacy ( Shen et al, 2017 ; Hohmann et al, 2020 ; Nie et al, 2021 ). However, while they can often improve symptoms, in many cases, pain, functional impairment, and reduced quality of life persist even after the injections.…”
Section: Discussionmentioning
confidence: 99%